2021
DOI: 10.1002/jcla.24166
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level EFCAB1 promoted progress by upregulated DNMT3B and could be as a potential biomarker in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) incidence is on the rise. We found that EFCAB1 (EF‐Hand Calcium Binding Domain 1) was significantly downregulated in LUAD tissues, but the mechanism of EFCAB1 is unknown. Methods One hundred and two LUAD samples and corresponding NT samples were prospectively collected from patients at the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, China, from August 2018 to August 2021.EFCAB1 expression was estimated in LUAD cells and tissues by qPCR. In‐vitro cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Glioma growth is slowed in vitro and in vivo experiments when a DNMT1 inhibitor is given ( 36 ). Currently, there is no specific research on DNMT3B in glioma, but DNMT3B has been reported to accelerate the occurrence and progression of esophageal cancer ( 38 ), lung cancer ( 39 ), breast cancer ( 40 ), and ovarian cancer ( 41 ), implying that DNMT3B is an essential biomarker in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma growth is slowed in vitro and in vivo experiments when a DNMT1 inhibitor is given ( 36 ). Currently, there is no specific research on DNMT3B in glioma, but DNMT3B has been reported to accelerate the occurrence and progression of esophageal cancer ( 38 ), lung cancer ( 39 ), breast cancer ( 40 ), and ovarian cancer ( 41 ), implying that DNMT3B is an essential biomarker in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%